Antimicrobial Effect of Platelet-Rich Plasma against Porphyromonas gingivalis. (13th May 2019) - Pham, Thuy Anh Vu; Tran, Thao Thi Phuong; Luong, Ngan Thi My
Abstract : Aim . The aim of our study was to evaluate whether there was a difference in antimicrobial effect between the PRP of healthy volunteers and that of patients with chronic periodontitis against P. gingivalis, which was fresh cultured from subgingival plaque. Methods . Subgingival plaque of patients with moderate and severe chronic periodontitis was collected to isolate P. gingivalis . The PRP of four individuals with healthy periodontium and four patients with moderate and severe periodontitis were collected with a specific kit using a two-centrifuge procedure, and then, the antibacterial properties against P. gingivalis were tested, through their minimum inhibitory concentration (MIC), adhesion resistance assay, and biofilm susceptibility assay. Results . P. gingivalis was successfully isolated from the subgingival plaque of the 21st patient. The round, smooth, and black colony appeared in the agar disk after 7–10 days of incubation under anaerobic conditions. Bacterial identification was performed by MALDI-TOF and confirmed by PCR. All PRP samples tested showed the ability to inhibit P. gingivalis growth. The MIC value (expressed as fraction of PRP) was 1/2, and PRP prevented P. gingivalis attachment on the disk surface. However, PRP did not have a strong effect on the suppression of P. gingivalis biofilm. Conclusion . PRP of individuals with healthy periodontium and chronic periodontitis patients showed antibacterial properties against P. gingivalis. This material can become an adjunct to periodontal treatment.